Aplikasi Pelayanan Pengaduan Masyarakat Berbasis Web pada Rumah Sakit Umum Daerah Langsa - Ayu Novira; Feri Fadli Aiyub (Puslitbang Sekawan Institute Nusa Tenggara, 2019)
Information technology is one of the things that has an important role in the era of globalization. Technological developments rapidly growth from year to year then its own facilities so as to provide convenience for its users. Information technology directly affects the lives of individuals and social especially at government agencies. Langsa General Hospital is one of the government agencies that has grown in the field of public health services, which is one of the public facilities are very important in the life of the community. It must be in balance with good services and facilities provided by the hospital. One of the facilities needed Area of Langsa General Hospital which is a container for the community can channel feedback in the form of a complaint with the objective as a means of communication between the hospital and the community which acts as a users of the service, with the existence of the container, the hospital can increase quality or improve any service provided to the community hospital.